2019
DOI: 10.1186/s13717-019-0184-6
|View full text |Cite
|
Sign up to set email alerts
|

Soil erosion affects variations of soil organic carbon and soil respiration along a slope in Northeast China

Abstract: Background: Although soil erosion plays a key role in the carbon cycle, a holistic and mechanistic understanding of the soil erosion process within the cycle is still lacking. The aim of this study was therefore to improve our mechanistic understanding of soil organic carbon (SOC) and soil respiration dynamics through an experiment conducted in an eroding black soil farmland landscape in Northeast China. Results: The depositional profiles store 5.9 times more SOC than the eroding profiles and 3.3 times more SO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…Soil erosion and SOC deposition along hillslopes can lead to spatial redistribution of SOC, i.e., the removal of soils that are rich in organic carbon from source hillslopes (shoulder and backslope) and their accumulation at the footslope (Wang et al, 2017). It has been confirmed that the SOC content in the cultivated areas of the Loess Plateau had the following distribution pattern: sedimentary area > stable area > eroded area (Wang et al, 2014a;Li et al, 2019). In our study, considering the first 30 cm, the SOC distribution along the hillslope after vegetation restoration followed a similar trend.…”
Section: Effect Of Vegetation Restoration On Soc Migration At the Soimentioning
confidence: 88%
See 1 more Smart Citation
“…Soil erosion and SOC deposition along hillslopes can lead to spatial redistribution of SOC, i.e., the removal of soils that are rich in organic carbon from source hillslopes (shoulder and backslope) and their accumulation at the footslope (Wang et al, 2017). It has been confirmed that the SOC content in the cultivated areas of the Loess Plateau had the following distribution pattern: sedimentary area > stable area > eroded area (Wang et al, 2014a;Li et al, 2019). In our study, considering the first 30 cm, the SOC distribution along the hillslope after vegetation restoration followed a similar trend.…”
Section: Effect Of Vegetation Restoration On Soc Migration At the Soimentioning
confidence: 88%
“…In some simulations in hillslope plots, the distribution of labile organic carbon varied markedly along slopes (Berhe and Torn, 2017), and most followed the trend: sedimentary area > stable area > eroded area (Doetterl et al, 2012;Patton et al, 2019;Wang et al, 2019). However, current research on the distribution of the SOC in the extension of slopes focuses primarily on agricultural land or grassland (Kirkels et al, 2014;Doetterl et al, 2016;Li et al, 2019). Vegetation restoration is recognized widely as an effective way to enhance SOC content and control soil erosion (Kim and Kirschbaum, 2015;Xin et al, 2016;Hancock et al,2019).…”
Section: Introductionmentioning
confidence: 99%
“…Third, previous studies have found that the concentrations of both soil organic C (Li et al 2019) and amino sugars (Ni et al 2020b) significantly varied at different depths. To allow valid comparisons to assess the influence of N addition on soil microbial necromass C from different studies, only the data from samples that were collected in the upper 20-cm layer of soils were included in our dataset.…”
Section: Data Compilationmentioning
confidence: 93%
“…The particle size distribution could also affect water storage/movement and this was higher in the forest gully bottom where there was a lower sand content. The high-moisture conditions at this largely depositional position would also limit decomposition rates and simultaneously stabilize SOC [54]. Li et al (2019) [54] suggested that depositional topsoil SOC is prone to mineralization (in consequence more CO 2 is emitted) while SOC is stabilized at subsoil depths.…”
Section: Characteristics Of the Forest Gully Soilmentioning
confidence: 99%